Automation System For Water Leakage Detection With PLC Omron and Arduino Uno and HMI NB10-TW01 Direct Digital Bit 8 Binary I/O - Desmayadi Desmayadi; Taswanda Taryo; Agus Sofwan; Sri Vidawati (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2024)
Abstract There are many challenges in operating a multi-story building so the building can operate well. One potential problem that has a serious risk of damaging assets and even causing disruption to building operations is water leaks. To detect the impact of leaks from water installations, a detection system is needed that can provide specific information about the location of the leak to the building control center. This system uses a water detector as detection and a digital direct bit module as 8-bit input to the PLC Omron CPM2A, then the PLC will send an 8-bit digital direct output signal to the Arduino Uno module and a graphic visualization display using the Omron NB10-TW001 HMI. This research method is to design hardware and software. Testing the accuracy of input and output (I/O) signals, testing detectors, power supplies, and relay modules. From the research results, it was found that the input and output signals correspond to the 8 I/O bits, namely 00000000 - 11111111 which are processed by the PLC and Arduino, the performance of the Water Detector functions well as proven by the functioning of the CRM. Keyword: Programmable Logic Controller (PLC); Water Detector (WD); Channel Relay Module (CRM); Human Machine Interface (HMI); Arduino Uno; Digital Direct Bit.